اﺛﺮ اﻟﺘﻌﺰﯾﺰ اﻻﯾﺠﺎﺑﻲ ﻓﻲ ﺟﺬب اﻻﻧﺘﺒﺎه اﻟﺒﺼﺮي ﻷطﻔﺎل اﻟﺮﯾﺎض (Journal of the College of Education for Women, 2019)
There are many teacher and parents suffer from reduce the ability of attention to the children, so the attention not settle on nothing not only to minute for time, so the research aim to following: 1-Is the using the positive reinforcement lunch in take attention of kindergarten visual? 2-1-Is the using the positive reinforcement article in take attention of kindergarten visual? 3-1-Is the using the positive reinforcement symbol in take attention of kindergarten visual? 4-1-Is the using the positive reinforcement action in take attention of kindergarten visual? 5-Is the using the positive reinforcement socialization in take attention of kindergarten visual? 6-what the most percentage obtain of the six factors of take attention? The chosen intention upon limited condition, the number of sample(72),(36)male and(36) female in kindergarten labrotory\Al-Rusafa in Al-Jaderia ,then chosen the level which is face the four years so the level of kindergarten is number(36)child's the researchers get the formation of children through the tips of evaluation for kindergarten, so the number of children which applies the instrument was (36),(16)male and(20)female, the instrument consist of visual attention measurement includes(6)pictures, each picture represent one factor of take attention visual from(6)factors. In the measurement achieve equivalent and validity and reliability after achieve the data confident statically ,so the result is following of : 1-The result shown the positive reinforcement(nut rain, symbol, action, and socialization) effect on take attention visual of kindergarten. 2- The result shown the positive reinforcement(article) the(pencils)effect on take attention visual of kindergarten. 3-The most percentage obtain the(change stimuli and and the movement stimuli). On light these result the researchers put some of suggestion and recommendations.